Exploiting Augmented Intelligence in Systems Engineering and Engineered Systems. Issue 1 (15th April 2020) - Madni, Azad M.
ABSTRACT: With AI resurgence paced by recent machine learning advances, several engineering disciplines including systems engineering turn to AI to improve system model accuracy, process flexibility, content exploration and search, and team productivity. More recently, AI has become a means to augment rather than replace human capability. This perspective alters AI's role from autonomous intelligence to augmented intelligence (AugI). Inherent in this view, recognizing AI and human together can perform certain tasks better than either could alone. This paper presents a methodological framework for effectively exploiting AugI in systems engineering and in engineered intelligent human‐machine systems.